Distinctions in early stage unwinding mechanisms of zwitterionic, capped, and neutral forms of different alpha-helical homopolymeric peptides - Pandey, Prithvi Raj; Roy, Sudip (Journal of Physical Chemistry B, 2012)
Molecular dynamics simulations of alpha-helical polyalanine, polyleucine, polylysine, and poly(glutamic acid) with different forms of terminal groups in water at 300 K showed sharp distinctions in their unwinding mechanisms. Zwitterionic, capped, and neutral forms of polyalanine, polyleucine, and polylysine have been explored to elucidate their unwinding mechanism at very early stage, e.g., initial time window. Role of water in the unwinding mechanisms of the various helices has been envisaged. Also, it is evident from our calculations that the short- and long-range nonbonded interactions among the side chains is an important factor determining the unwinding mechanisms of the various homopolymeric alpha-helices. These findings can be helpful in constructing predictive models for understanding of the unwinding of alpha-helical proteins and peptides.